Dose–Response Matters! – A Perspective on the Exercise Prescription in Exercise–Cognition Research - Herold, Fabian; Müller, Patrick; Gronwald, Thomas; Müller, Notger G. (Frontiers in Psychology, 2019)
In general, it is well-recognized that both acute physical exercises and regular physical training influence brain plasticity and cognitive functions positively. However, growing evidence shows that the same physical exercises induce very heterogeneous outcomes across individuals. In an attempt to better understand this interindividual heterogeneity in response to acute and regular physical exercising, most research, so far, has focused on non-modifiable factors such as sex and different genotypes, while relatively little attention has been paid to exercise prescription as a modifiable factor. With an adapted exercise prescription dosage can be made comparable across individuals, a procedure which is necessary to better understand the dose-response relationship in exercise-cognition research. This improved understanding of dose-response relationships could help to design more efficient physical training approaches against, for instance, cognitive decline.